The Vertical Profile Of Nitrate and Orthophosphate in Pinang Luar Oxbow Lake Buluh China Village Siak Hulu Sub District Kampar District Riau Province - Cristy Artha D Sinurat; Madju Siagian; Asmika Harnalin Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research has been done in Pinang Luar Oxbow Lake from Mei-Juni2013. This research aims to understand the vertical profile of nitrate andorthophosphate in Pinang Luar oxbow lake. The research used survey method.Sample were taken in three stations, namely station 1, station 2 and station 3.Sampling vertical based on depth, at surface, 1,5 secchi disk, 2,5 secchi disk, andin the bottom. The parameters of water quality measured nitrate, orthophosphate,temperature, brightness, depth, current, pH, and dissolved oxygen (DO). Theresult shown concentration of nitrate range of 0,030 - 0,123 mg/l, and theconcentration of orthophosphate range of 0,013 – 0,040 mg/l. The value oftemperature is 310C, transparency range of 65 – 70 cm, depth range of 261,7 –461,7 cm, current range of 2,57 -3,24 cm/second. The concentration of dissolvedoxygen (DO) range of 1,87 – 6,4 mg/l. The value of pH is 6. The vertical profileof nitrate and orthophosphate showed increased with the increment of depth. Theparameters of water quality were observed still support the aquatic organisms.Keywords : nitrate and orthophosphate, the vertical profile, Pinang Luar Oxbow